Penelitian Pendahuluan Angkutan Sedimen Melayang Sub-Das Citarik Hulu = (Suspended Sediment Transport in the Upper Citarik Sub-River Basin: A Preliminary Study - Soewarno Soewarno (Majalah Geografi Indonesia, 1988)
Apart from its function as a soil cover, forest also plays a positive role in preserving water and sediment in a river basin. Rain water which is abundant in the rainy season is caught and stored underground, so that the erosion and flood hazard can be eliminated. In the dry season groundwater becomes reservation to minimize and even eliminate the risk of water shortage. This preliminary study is to monitor suspended sediment transport with respect to the forest area of upper Citarum River Basin at upper Citarih Sub - River Basin. On the basis of the preliminary study results, it can be said that for a river basin where percentage of the forest area is smaller (i) the suspended sediment concentration is higher and (ii) the total sediment per area unit is greater. These indications were found during the study period, from September 1987 to February 1988. The preliminary study was conducted in a sub-river basin where the soil type is a mixture of andosol and brown regosol, and the terrain is undulating, hilly to mountainous with slope more than 15 percent.